To Manage Fisheries with Complexity and Chaos Theories - Ferreira, M. A. M.; Filipe, J.; Coelho, M.; Pedro, M. I. (EasyChair Preprint Nº 10689, 2025)
Chaos theory - and models related to non-linear dynamic systems - has increased its importance last decades. In fact, chaos is one of the concepts that most rapidly have expanded in what research topics respects. Chaos is ordinarily disorder or confusion; scientifically it represents a disarray connection, but basically it involves much more than that. Change and time are closely linked, and they are essential when considered together as chaos theory foundations are intended to be understood. Given the large number of applications in several areas, the goal of this work is to present chaos theory - and dynamical systems such as the theories of complexity - in terms of the interpretation of ecological phenomena. The theory of chaos applied in the context of ecological systems, especially in the context of fisheries, has allowed the recognition of the relevance of this kind of theories to explain fishing events. It raised new advances in the study of marine systems, contributing to the preservation of fish stocks.